PENGARUH KOMUNIKASI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Kentucky Fried Chicken Cabang Manahan Solo) - Sutarno, Wiwin Setyorini, Lamidi & (Universitas Slamet Riyadi, 2018)
This research aims to analyze the significance of the influence of communication, motivation and partially working environment as well as the simultaneous performance against Kentucky Fried Chicken Branch Manahan Solo. This study used a survey method, the type of data the data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this study are all employees of a KFC Branch Manahan Solo totalling 52 employees, the number of samples that used as many as 52 employees, so it is a research census. Methods of data collection were used: questionnaire and documentation. Technique of data analysis used the test of validity, reliability test, test the assumption of linear regression analysis, classic double, t test, F test and coefficient of determination. The results showed that significant influential communication employee performance against Kentucky Fried Chicken Branch Manahan Solo. Significant effect on performance the motivation of employees. Significant influential work environment on performance of employees. Communication, motivation and work environment simultaneously influential employee performance significantly to Kentucky Fried Chicken Branch Manahan Solo.Keywords: communication, motivation, work environment, the performance of employees.